Comparison of the incidence and clinical presentation of preterm birth less than 34 weeks gestation University hospitals in Dublin, Ireland and Denver, Colorado, USA. Issue 3 (2015) - Hoffman, M. Camille; Mahony, Rhona; Foley, Michael; Gibbs, Ronald S.; Galan, Henry L.; Lynch, Anne M.
No abstract available